2016
DOI: 10.1016/j.soscij.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Does family structure affect children's academic outcomes? Evidence for Spain

Abstract: Available online xxx JEL classification: I21 J12 C21 Keywords:Family structure Academic achievement Propensity score matching School ownership a b s t r a c t Several sociodemographic phenomena have changed family organization in Spain over the last few decades, where less structured forms than the traditional nuclear family have gained in importance. In view of the importance of children's and adolescents' education, we aim to identify the effect of non-nuclear family membership on academic outcomes of Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
1
3
0
12
Order By: Relevance
“…The bivariate findings showed that the levels of reported commitment to school and learning were significantly higher among young people in care whose biological parents were married than among those whose parents were divorced or separated. This finding is consistent with the literature on children in the general population, which suggests that, on average, children whose parents are divorced perform less well in a range of psychosocial and educational spheres than children living with both biological parents (Amato, 2010; Aughinbaugh et al, 2005; Frisco et al, 2007; Hampden-Thompson, 2013; Santín & Sicilia, 2016; Sobolewski & Amato, 2007). Studies of children in care have had similar findings (Attar-Schwartz, 2008; Vorria et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The bivariate findings showed that the levels of reported commitment to school and learning were significantly higher among young people in care whose biological parents were married than among those whose parents were divorced or separated. This finding is consistent with the literature on children in the general population, which suggests that, on average, children whose parents are divorced perform less well in a range of psychosocial and educational spheres than children living with both biological parents (Amato, 2010; Aughinbaugh et al, 2005; Frisco et al, 2007; Hampden-Thompson, 2013; Santín & Sicilia, 2016; Sobolewski & Amato, 2007). Studies of children in care have had similar findings (Attar-Schwartz, 2008; Vorria et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…On average, children whose parents are divorced perform less well in a range of spheres, including emotionally, behaviorally, and academically, than children living with both biological parents (Amato, 2010). For example, Frisco, Muller, and Frank (2007) found that adolescents whose parents are separated or divorced experienced poorer academic achievement, including lower grades and more course failures (see also Aughinbaugh, Pierret, & Rothstein, 2005; Hampden-Thompson, 2013; Santín & Sicilia, 2016; Sobolewski & Amato, 2007). There is evidence that, on average, the presence of two parents makes it easier for young people to obtain help with their homework, to obtain emotional support when needed, to enjoy a sense of family unity which facilitates performing well academically, and to grow intellectually as a result of interacting with available close adults (Astone & McLanahan, 1991; Jeynes, 2005).…”
Section: The Moderating Role Of Divorce In the Link Between Father An...mentioning
confidence: 99%
“…A la hora de adquirir estas competencias, numerosos estudios afirman que el contexto sociofamiliar del alumnado incide significativamente sobre su rendimiento académico (Castro et al, 2015;Kim & Hill, 2015;Vázquez et al, 2020). Entre otros factores, la formación académica, así como un nivel cultural elevado, influyen positivamente en el rendimiento de los hijos (Santín & Sicilia, 2016). Asimismo, Castro et al (2015) encontraron que las mayores asociaciones entre rendimiento académico y factores familiares se dan cuando los progenitores tienen mayores expectativas académicas y se involucran en las actividades escolares y en el desarrollo de hábitos lectores.…”
Section: Introductionunclassified
“…The effect of family structure on educational outcomes has continued to elicit a lot of interest among scholars (Browne & Battle, 2018;Frisco, Muller, & Frank, 2007;Hampden-Thompson, 2013;Heard, 2007;Santin & Sicilia, 2016;Sun & Li, 2011;Wu, Schimmele, & Hou, 2015). Some scholars have tended to agree that it has a significant effect (Browne & Battle, 2018;Case, Lin, & McLanahan, 2001;Ermisch & Francesconi, 2001;Evenhouse & Reilly, 2004;Frisco et al, 2007;Ginther & Pollak, 2004;Heard, 2007;Sun & Li, 2011) and that the link is causal (Amato, Patterson, & Beattie, 2015;Frisco et al, 2007).…”
Section: Introductionmentioning
confidence: 99%